Pemerataan Pendidikan: Studi Kasus 34 Provinsi di Indonesia - Riris Sihombing (Jurusan Ilmu Ekonomi Universitas Katolik Parahyangan, 2022)
Education is essential in improving the quality of human capital and social equity in income. However, the critical role of education still needs to be matched by equal access to education for all people in every region. The research wanted to determine education inequality in 34 Indonesian provinces from 2015 to 2019. This research also identified whether or not there was an influence between education funds, education infrastructure, and the average income level on the education gini. The results obtained show that there is a high educational disparity between the western and eastern regions of Indonesia. Using the Panel Least Square (PLS) technique, the results show that education funding and infrastructure have a negative and significant relationship. Meanwhile, the income variable has a positive relationship, but the results are insignificant.